Investigation of Dimensional and Physical Properties of Eri Silk Bi-Layer Knit Fabrics for Active Wear Applications. Issue 6 (November 2021) - Kumar, T. Sathish; Kumar, M. Ramesh; Kumar, B. Senthil
The knitwear industry caters to the needs of the modern youth, whose preferences vary according to the trends and tastes of the modern age. This paper endeavors to demonstrate that active wear fabrics made of eri silk have very good physical properties. The main objective of this research is to investigate dimensional and physical properties of plated interlock, mini-flatback rib, and flatback rib structures developed with two different yarn counts (30s and 40s). The dimensional and physical properties of those samples are investigated in terms of dimensional stability, spirality, bursting strength, elongation percentage, fabric areal density, and fabric thickness. Variables such as yarn count and knit structure play a significant role on the dimensional and physical properties of the fabric.